(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2020)
Modern Indian theatre in English and translation witnessed a significant transformation in the latter half of the twentieth century, and Girish Karnad stands at its forefront. His dramaturgy engages myth, folklore, and history not merely as aesthetic devices but as critical frameworks to interrogate contemporary social realities. Although Karnad does not explicitly position himself as a feminist playwright, his works reveal deep sensitivity toward women’s marginalization and their quest for identity within patriarchal structures.